Geometric Morphometrics of Astragalus and Shape Variation Analysis in Capra, Ovis, and Bovidae - Yasemin Üstündağ; İftar Gürbüz; Yasin Demiraslan; Özcan Özgel (Veterinary Medicine and Science)
ABSTRACT In the study, it was investigated whether taxonomic differences have an effect on shape using bovine, ovis, and capra astragalus. A total of 142 samples, 32 bovine (Holstein), 71 ovis (Merino ovis), and 39 capra (Hair goat) astragalus, were used as material. The geometric morphometry method was applied in the study. 13 homologous landmarks were marked on the photographed astragalus. Principal component analysis was performed on the new coordinates obtained as a result of Procrustes analysis. In addition, in areas where shape differences were concentrated, allometric effect and grouping features were determined. The MorphoJ program was used for all these analyses. As a result, 22 principal components were calculated for astragalus. In terms of PC1, capra samples were placed between bovine and ovis sample clusters. Most of the shape variations were formed on the medial side of the astragalus. In conclusion, ovis and bovine astragalus samples were grouped taxonomically completely (100%) separately, while capra samples were grouped largely (97.2%) separately between ovis and capras in cross‐validation scores. The results are important in terms of contributing to taxonomy, morphology, and zooarcheology studies.